UGT1A1 gene polymorphisms and jaundice in Indonesian neonates - Rinawati Rohsiswatmo; Radhian Amandito; Andiani Wanda Putri; Nilam Sartika; Amarila Malik (Indonesian Pediatric Society, 2019)
Background Uridine diphospho-glucuronocyltransferase 1A1 (UGT1A1) polymorphisms are a risk factor for unconjugated hyperbilirubinemia in neonates. UGT1A1 polymorphisms decrease bilirubin conjugation, thus causing hyperbilirubinemia. A variety of polymorphisms have been reported, with UGT1A1*60 and UGT1A1*6 especially prominent in the Asian population. Hyperbilirubinemia polymorphism studies are lacking in Indonesian populations. Objective To identify UGT1A1*60 and UGT1A1*6 profiles in Indonesian populations of heterogeneous ethnicity. Methods We enrolled 42 jaundiced neonates who were born from January to April 2017 and treated in the Neonatal Intensive Care Unit of our national referral center, Cipto Mangunkusumo Hospital, Jakarta, Indonesia. Genetic mutations *60 of exon 1 and *6 of the promoter region were analyzed by polymerase chain reaction – restriction fragment length polymorphism methods, with DraI and AvaII as restriction enzymes, respectively. Clinical data including total serum bilirubin and racial information were obtained by medical records and interviews with parents. Results There were no homozygous mutations of UGT1A1*6, but 4.8% of subjects were heterozygous. As for UGT1A1*60, 4.8% were heterozygous and 95.2% were homozygous. Racial variations were not observed for UGT1A1*60, while Betawi descendents were found to have many heteroygous forms of UGT1A1*6. Conclusion Polymorphisms of the UGT1A1 gene were found in Indonesian neonates. Some ethnicities also showed increased tendency towards its incidence, such as the heterozygous form of UGT1A1*6.